Retrieval of haze properties and HCN concentrations from the three-micron spectrum of Titan. (May 2018) - Kim, Sang J.; Lee, D.W.; Sim, C.K.; Seon, K.I.; Courtin, R.; Geballe, T.R.
Highlights: A new analysis of the 3 µm HCN emission spectrum of Titan for altitudes below 500 km. Present a formulation for the radiative transfer of single dust and molecular scattering. Derive vertically-resolved single scattering albedos of the Titanian haze. Present mixing ratios of HCN, and compare them with the literature values. Abstract: The 3 µm spectrum of Titan contains line emission and absorption as well as a significant haze continuum. The line emission has been previously analyzed in the literature, but that analysis has not properly included the influence of haze on the line emission. We report a new analysis of the 3 µm HCN emission spectrum using radiative transfer equations that include scattering and absorption by molecules and haze particles at altitudes lower than 500 km, where the influence of haze on the emergent spectrum becomes significant. Taking advantage of the dominance of resonant single scattering in the HCN ν3 fundamental and of the moderate haze optical thickness of the atmosphere around 3 µm, we adopt single dust and molecular scattering and present a formulation for the radiative transfer process. We evaluate the quantitative influence of haze scattering on the emission line intensities, and derive vertically-resolved single scattering albedos of the haze from model fits. We also present the resulting concentrations of HCN for altitudes below 500 km, where we find that the haze scattering significantly influences the retrieval of the concentrations of HCN. We conclude that the formulation we present is useful for the analysis of the HCN line emission from Titan and other similar hazy planetary or celestial objects.